La representación de Andalucía en la guía Routard / Trotamundos (Altre Modernità, 2012)
A travel guide author bases their writing on the notions they have developed of the would-be traveller and therefore chooses appropriate subject matter which will encourage the traveller to a have a new experience.  In order to reach their goal, the author selects the linguistic and discourse strategies that will best help to persuade the reader to visit a place.  The Routard/Trotamundos guide, which is the object of this present study, aims to reject the linguistic and discourse stereotypes underlying the conventions of the genre.  It therefore proposes a fresh and more realistic vision of a destination.Moreover, the study of the Spanish and Italian versions allows us to reflect on the way a place is perceived, both from the viewpoint of the culture which is making the observations, and also from the culture which is being observed (Amossy 1994: 75).  Both cultures can use the same words but with different meanings.
Keywords: discourse analysis; stereotypes; textual genres; tourism